Opinion 2407: Bulimus rupestris Philippi, 1836 (Gastropoda, Stylommatophora, Chondrinidae): conservation of the specific name - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has used its plenary power to rule that the specific name of Bulimus rupestris Philippi, 1836 is not invalid by reason of it being a junior primary homonym of the specific name of Bulimus rupestris Krynicki, 1833.